Hubungan Gaya Kepemimpinan Kepala Ruang Dengan Kinerja Perawat Di Ruang Rawat Inap Rsud Ahmad Yani Metro Lampung - Tiandani, Zulfian; Mudayana, Ahmad Ahid (STIKES Wira Husada Yogyakarta, 2015)
ABSTRACT The behavior of nurses who come and do not go home on time, the office hours are not in place for various reasons beyond the task can degrade the performance of nurses. Leadership style required a hospital room Ahmad Yani Hospital Metro Lampung adar be motivating nurses and nurses performance. This study aims to analyze the relationship between leadership style performance space with nurses in inpatient hospitals Ahmad Yani Metro Lampung. This type of cross sectional analytic study. The study population is a nurse in the hospital inpatient Ahmad Yani Metro Lampung many as 172 people with a total sample of 51 people. Measuring instrument in the form of a questionnaire study. Analysis of the data using a hypothesis test between two variables. The results showed an autocratic leadership style as much as 96.1% lower category and 3.9% higher. Laissez faire leadership style category as much as 94.1% lower and 5.9% higher. Democratic leadership style category as much as 96.1% higher and 3.9% lower. Nurse performance category as much as 90.2% higher and lower by 9.8%. There is a relationship between autocratic leadership style, laissez faire leadership style, democratic leadership style with the performance of nurses in Inpatient Hospital Ahmad Yani Metro Lampung.